The Use Of Polyhydroxyalkanoate Synthase (Phacbp-M-Cpf4) And Newly Identified Enoyl-Coa Hydratase (Phajss) For The Production Of Poly[(R)-3-Hydroxybutyrate-Co-(R)-3-Hydroxyhexanoate] - Tan, Hua Tiang (2020)
Most industrial plastics are produced using non-renewable resources such as petroleum. Hence, polymer production processes based on renewable resources must be developed to reduce the carbon footprints left by human activities. Polyhydroxyalkanoates (PHAs) are intracellular biopolyesters synthesized by numerous microorganisms as carbon storage under culture conditions of limiting essential nutrients but with excess carbon source. Besides, PHA is biodegradable. Among the various types of PHA, poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] [P(3HB-co-3HHx)] has a high potential to serve as a commercial bioplastic due to it having the most identical properties to petroleum-based plastics. PHA synthase of Chromobacterium sp. USM2 (PhaCCs) and PHA synthase isolated from mangrove metagenome (PhaCBP-M-CPF4) have been reported to be able to produce P(3HB-co-3HHx). In this study, PhaCCs and PhaCBP-M-CPF4 as well as enoyl-CoA hydratase of Streptomyces sp. strain CFMR 7 (PhaJSs) were characterized. Thus, five different genotypes of Cupriavidus necator transformants harboring phaCBP-M-CPF4 gene and three different genotypes of C. necator transformants harboring phaCCs gene were developed to evaluate the incorporation efficiency of 3-hydroxyhexanoate (3HHx) monomers. The amount of 3HHx monomer incorporated in the PHA synthesized by these C. necator transformants were examined using palm oil as the sole carbon source. PhaCBP-M-CPF4 enabled the incorporation of higher 3HHx monomer than PhaCCs (up to 18 mol% 3HHx). Besides, the molecular weight (Mw) of P(3HB-co-3HHx) produced by transformants harboring phaCBP-M-CPF4 could reach up to 1.8 × 106 Da, which was six times higher than the P(3HB-co-3HHx) produced by transformants harboring phaCCs. Enoyl-CoA hydratase is crucial for 3HHx accumulation during the production of P(3HB-co-3HHx). This enzyme channels the pathway for supplying (R)-3-hydroxyacyl-CoA monomer units, especially (R)-3-hydroxyhexanoyl-CoA from fatty acid β-oxidation. In this study, phaJSs was identified from the rubber degrading Gram-positive non-PHA producing bacterium, Streptomyces sp. strain CFMR 7. Co-expression of this enoyl-CoA hydratase gene with the chosen PhaC above, phaCBP-M-CPF4, in C. necator PHB¯4, significantly increased 3HHx composition without decreasing the PHA content. This transformant could produce P(3HB-co-3HHx) with 18 mol% of 3HHx and has a Mw of nearly one million Da revealing that both PhaCBP-M-CPF4 and PhaJSs could potentially be used for industrial applications.